Participative Leadership and Shared Facility Management: An Integrated Model for Conducive Learning Environments - Rica Agus Budiyanto; Sri Handayani (Dinasti International Journal of Education Management and Social Science, 2025)
This study rigorously examines the implementation of participative leadership in the intricate context of shared facility management within multi-unit elementary school complexes, specifically focusing on the SDN Tegal Alur Complex. Employing a qualitative phenomenological approach, the research deeply probes the subjective experiences and perceptions of school principals, teachers, and administrative staff concerning interschool collaboration in resource allocation and maintenance. The investigation reveals a highly effective and robust operational model that synergistically integrates Rensis Likert's Participative Management Theory with W. Edwards Deming's Plan-Do-Check-Act cycle. This integrated framework's success is attributed to several key elements: active stakeholder participation in decision-making processes, which significantly fosters inclusivity and prevents conflicts; the establishment of transparent and responsive two-way communication channels; and the cultivation of a profound sense of ownership and collective responsibility among all parties, leading to voluntary maintenance and ethical usage. Furthermore, the pivotal "linking-pin" role played by school principals ensures seamless coordination and mediation between the autonomous school units, while the institutionalized PDCA-based evaluation and follow-up mechanism drives continuous improvement and adaptive problem-solving, effectively addressing challenges such as noise disturbances. This research critically addresses a significant gap in the literature regarding the systematic integration of leadership theories and facility management practices in shared educational settings. It offers an empirically derived, adaptable operational model that not only enhances resource efficiency but also actively promotes a collaborative culture, ultimately contributing to a more conducive and sustainable learning environment across multiple schools.